Boron as a Context-Dependent System-Level Modulator: Mechanisms and Implications in Chronic Diseases - Tuzcu, Mehmet; Ozmen, Ramazan; Ali, Shakir; Sahin, Kazim (Springernature, 2026)
Boron is a biologically active trace element essential to plants and is increasingly recognized as a potentially important modulator of human physiology. This critical narrative review evaluates evidence concerning mineral metabolism, endocrine-related pathways, redox balance, immune signaling, neurological function, cardiometabolic health, osteoarticular disorders, host-microbiome interactions, and boron-containing pharmaceuticals. Boron's Lewis acid properties and its ability to form reversible complexes with cis-diol-containing biomolecules provide a plausible basis for its broad biological effects, including interactions with NAD(+)- and S-adenosylmethionine-related pathways, membrane-associated glycoconjugates, and inflammatory signaling networks. Experimental and limited clinical studies suggest that boron intake at the doses evaluated may influence bone mineralization, vitamin D metabolism, selected endocrine-related biomarkers, antioxidant defense, and inflammatory homeostasis. In parallel, boron-containing compounds have emerged as valuable pharmacological scaffolds, as illustrated by boron-based agents used in oncology, dermatology, infectious disease, and boron neutron capture therapy. However, despite promising mechanistic and translational findings, evidence for boron's strict essentiality in humans remains limited, and no indispensable boron-dependent human pathway has yet been established. Recent concepts, such as conditional essentiality, suggest that boron may become biologically relevant in specific nutritional, metabolic, inflammatory, skeletal, or microbiome-related contexts. Nevertheless, small sample sizes, short intervention periods, heterogeneous formulations, and reliance on surrogate endpoints continue to constrain clinical interpretation. Future studies require speciation-resolved dosing, pharmacokinetic monitoring, adequately powered randomized designs, long-term safety assessment, and clinically meaningful outcomes. Overall, boron represents a promising but incompletely defined trace element at the intersection of nutrition, immunometabolism, host-microbiome biology, and therapeutic drug design.
Keywords: Boron; Chronic Disease; Inflammation; Oxidative Stress; Bone Metabolism; Cardiometabolic Health